2018
DOI: 10.1108/ijlma-05-2017-0109
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Tier-1 capital, risk management, and profitability on performance of Indonesian Commercial Banks

Abstract: Purpose This research aims to examine the effect of Tier-1 capital, risk management, and profitability on performance of Indonesia commercial banks. Design/methodology/approach The research population consisted of all commercial banks listed in the Indonesia Stock Exchange periods of 2010 to 2014 with a total of 42 companies. The statistical analysis for testing the hypothesis using structural equation modeling (SEM) covariance based using WarpPLS. Findings Research result shows that Tier-1 capital has a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Regulators set minimum capital requirements to ensure banks can withstand financial distress. Sari et al (2018) discovered that tier-1 capital had a negative impact on profitability while having no effect on firm performance. This indicated that banks maintaining and increasing tier-1 capital could limit loan portfolio expansion, subsequently impacting firm performance.…”
Section: Bank Capital Adequacy Ratio On Firm Valuementioning
confidence: 99%
“…Regulators set minimum capital requirements to ensure banks can withstand financial distress. Sari et al (2018) discovered that tier-1 capital had a negative impact on profitability while having no effect on firm performance. This indicated that banks maintaining and increasing tier-1 capital could limit loan portfolio expansion, subsequently impacting firm performance.…”
Section: Bank Capital Adequacy Ratio On Firm Valuementioning
confidence: 99%
“…Many previous studies focussed on the relationship between bank-specific characteristics and performance in different countries (Tan et al , 2017; Al-Homaidi et al , 2018; Almaqtari et al , 2018; Bouzgarrou et al , 2018; Al-Harbi, 2019). In Indonesia Sari et al (2018) and Jumono (2019) analyzed the determinants of bank profitability but did not investigate differences between bank types. Atahau and Cronje (2014), Atahau (2015), Atahau and Cronje (2017), (2019) and Atahau et al (2019) have addressed the differences between bank-ownership types, however the studies focussed on the loan portfolios and returns of different ownership type banks in Indonesia.…”
Section: Introductionmentioning
confidence: 99%